Integrating Maqasid al-Shari’ah in Contemporary Islamic Legal Reform on Drug Policy - Andri Winjaya Laksana; Muhammad Ridwan Lubis; Denny Suwondo; Muhammad Ngazis; Ratih Mega Puspa Sari (Faculty of Sharia, IAIN Metro, 2025)
This research explores how contemporary Islamic legal reform shapes drug policy using the framework of Maqasid al-Shari’ah. In many Muslim-majority countries, drug-related problems are on the rise, and traditional punitive responses—such as mandatory death sentences and corporal punishment—are increasingly questioned for being ineffective and misaligned with core Islamic values. Using a qualitative-normative approach combined with comparative analysis, this study examines statutory frameworks, fatwas, and recent legal reforms in countries like Malaysia, Indonesia, and Iran. It highlights a growing shift toward maqasid-based reasoning in designing more balanced and humane drug policies. The findings reveal three key trends. First, there is increasing emphasis on hifz al-nafs (protection of life) and hifz al-‘aql (protection of intellect), reframing drug offences not merely as moral or legal violations but as public health concerns requiring systemic solutions. Second, several Islamic legal institutions are adopting harm reduction strategies—such as rehabilitation, decriminalisation of minor drug use, and reintegration programs—framed within the maqasid discourse to uphold human dignity and promote social welfare (maslahah ‘ammah). Third, there is a growing openness toward contextual ijtihad, allowing reinterpretation of hudud and ta'zir punishments considering contemporary realities and scientific evidence. Academically, this research contributes to Islamic legal studies by offering a systematic and comparative analysis of how the principles of Maqasid al-Shari’ah are being operationalised in modern drug policy reform. It fills a gap in the literature by bridging classical Islamic legal theory with contemporary policy needs, particularly in areas often neglected by traditional fiqh discourse, such as drug rehabilitation and public health. The study also advances the methodological integration of maqasid-based reasoning with empirical policy analysis, providing a practical framework for future legal reforms in Muslim-majority contexts.